After Tupac & D Foster - Woodson, Jacqueline (New York : Putnam's, 2008)
In the New York City borough of Queens in 1996, three girls bond over their shared love of Tupac Shakur's music, as together they try to make sense of the unpredictable world in which they live.
Newbery Medal/Honor.
School Library Journal starred.
Wilson's Junior High School.
Book Links (A.L.A.), January 2010.
Booklist, February 2008.
Bulletin (Center for Children's books), January 2008.
Keywords: Shakur, Tupac, -- 1971-1996 -- Juvenile fiction; Shakur, Tupac, -- 1971-1996 -- Fiction; Shakur, Tupac, -- 1971-1996 -- Fiction; African Americans -- Juvenile fiction; Friendship -- Juvenile fiction; African Americans -- Fiction; Coming of age -- Fiction; Friendship -- Fiction; African Americans -- Fiction; Bildungsromans; Friendship -- Fiction; Queens (New York, N.Y.) -- Juvenile fiction; Queens (New York, N.Y.) -- Fiction; Queens (New York, N.Y.) -- Fiction